Empirical Analysis of Good Corporate Governance and Firm Value on Sharia Banking in Indonesia - Eka Anan Kubota; Rossje V Suryaputri (CV. Syntax Corporation Indonesia, 2023)
The position of Islamic banking in Indonesia still needs improvement because currently the market share of Islamic banking is only 6.52% of the entire proportion of national banking. So that the government seeks to improve by launching the Roadmap for the Development of Indonesian Sharia Banking (RP2SI) 2020-2025. However, there are things that hinder the accelerated growth of the sharia banking business, including the absence of significant business model differentiation, sub-optimal quality and quantity of human resources. So that GCG analysis is needed to increase the value of Islamic banks. The purpose of this study is to see how much influence the GCG has on firm value using PBV theory. The research method used in this study is multiple linear regression analysis with secondary data of 13 Islamic Commercial Banks in Indonesia in 2017-2021. The results show that the Audit Committee, Corporate Governance Committee, and Risk Management Committee have a significant effect on firm value. Meanwhile, the Board of Commissioners, Remuneration and Nomination Committee, Risk Monitoring Committee and Institutional Ownership have no effect on company value.